Board Of Directors Characteristics And Firms Performance Among Jordanian Firms, Proposing Conceptual Framework - Mohammed Hassan Makhlouf; Nur Hidayah Laili; Mohamad Yazis Ali Basah (International Journal of Technical Research and Applications (IJTRA), 2024)
Volume-2, Special Issue 4 (July-Aug 2014), PP. 18-23